Endless seasons - Badovinac, Emily, author; Morales, Juan, advisor; Taylor, Cynthia, committee member; O'Connor, John, committee member (Colorado State University. Libraries, 2013)
Endless Seasons is a short novel that presents an example of enduring female friendship for the feminist literary canon. While examples of exceptional male friendship, also called heroic friendship, abound in the primary canon, female writers and subjects in contemporary American literature tend away from even an echo of what is presented by and for males. Endless Seasons takes one more step forward and provides this example of enduring female friendship in a rich multi-cultural setting where female silences are explored within religion and culture as the main character, Isabelle "Izzy" Juarez, traverses between childhood and womanhood. Endless Seasons is meant to make way for American female authors to rediscover virtue in the female bond, where love, acceptance, comfort and loyalty defeat the prototypical jealousy and betrayal within literary female friendships.
Keywords: novel; creative